2020
DOI: 10.1080/15228916.2020.1838835
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Motivations, Opportunities, and Challenges: An International Perspective

Abstract: The current entrepreneurship research has primarily focused on external environmental factors that influence enterprise development in developed economies, whilst studies from developing economies are lagging. Yet, evidence from the World Bank and Global Entrepreneurship Index suggest that entrepreneurship practice in developing economies has peaked. Using semistructured interview data from twenty entrepreneurs in The Gambia, we examined their motivations for entrepreneurship, the market opportunities and chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…In this context, the current paper significantly contributes to the study of the entrepreneurial motivation–intention relationship. First, the study expands and enriches the focus on different psychological and contextual factors that foster entrepreneurial motivations among university students (Kah et al, 2021; Wu and Mao, 2020). Second, entrepreneurial motivations, which spark the intention to undertake an entrepreneurial activity, play a vital role in the venture creation process (Barba-Sánchez and Atienza-Sahuquillo, 2018; Hassan et al, 2021; Meoli et al, 2020).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In this context, the current paper significantly contributes to the study of the entrepreneurial motivation–intention relationship. First, the study expands and enriches the focus on different psychological and contextual factors that foster entrepreneurial motivations among university students (Kah et al, 2021; Wu and Mao, 2020). Second, entrepreneurial motivations, which spark the intention to undertake an entrepreneurial activity, play a vital role in the venture creation process (Barba-Sánchez and Atienza-Sahuquillo, 2018; Hassan et al, 2021; Meoli et al, 2020).…”
mentioning
confidence: 94%
“…Other studies have found that the intention and behavior are highly correlated. Additionally, psychological and contextual factors play a pivotal role in fostering the motivations (Kah et al, 2021; Wu and Mao, 2020) that guide an individual toward an entrepreneurial activity (Hassan et al, 2021; Barba-Sánchez and Atienza-Sahuquillo, 2018).…”
mentioning
confidence: 99%
“…However, Hofstede (1980) indicates that the bias of certain cultures does not affect the creation of entrepreneurs. However, external environmental factors affect entrepreneurs' intentions to set up businesses (Bruno and Tyebjee 1982;Kah et al 2020). The characteristics of the place and time where entrepreneurs live affect entrepreneurial intentions (Hart et al 1995;Mehtap 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Every opportunity in business will come with challenges that will make entrepreneurs create more ideas and plan to survive. SMEs agreed that low operating cost is an opportunity in startup business (Kah et al, 2022). Direct costs of goods sold (COGS) and other operational costs, also known as selling, general, and administrative (SG&A), are included in operating costs.…”
Section: An Opportunities For Smes In Tourismmentioning
confidence: 99%